2019
DOI: 10.1038/s41598-019-48300-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin-mediated Processing of Uromodulin is Crucial for Salt-sensitivity and Thick Ascending Limb Homeostasis

Abstract: Uromodulin is a zona pellucida-type protein essentially produced in the thick ascending limb (TAL) of the mammalian kidney. It is the most abundant protein in normal urine. Defective uromodulin processing is associated with various kidney disorders. The luminal release and subsequent polymerization of uromodulin depend on its cleavage mediated by the serine protease hepsin. The biological relevance of a proper cleavage of uromodulin remains unknown. Here we combined in vivo testing on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 40 publications
(65 reference statements)
2
53
0
1
Order By: Relevance
“…The expression of uromodulin modulates the activity of NKCC2 and ROMK in the TAL 7,19 , and its deletion in mouse leads to a discrete salt-losing phenotype 35 . We recently showed that defective processing of uromodulin (due to hepsin mutation) is causing TAL dysfunction and salt wasting 36 . All these effects could contribute to the tubular dysfunction typically observed in patients with Bartter syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of uromodulin modulates the activity of NKCC2 and ROMK in the TAL 7,19 , and its deletion in mouse leads to a discrete salt-losing phenotype 35 . We recently showed that defective processing of uromodulin (due to hepsin mutation) is causing TAL dysfunction and salt wasting 36 . All these effects could contribute to the tubular dysfunction typically observed in patients with Bartter syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, however, hepsin is dispensable for embryonic development, postnatal survival, and liver regeneration (19,20). In addition to the liver, hepsin is expressed, at lower levels, in the kidney and inner ears, where hepsin is implicated in uromodulin processing and auditory nerve development, respectively (21)(22)(23). Moreover, hepsin upregulation has been found in many human cancers, including prostate, kidney, breast, and ovarian cancers (15,24), suggesting a role of hepsin in promoting tumor invasion and metastasis.…”
mentioning
confidence: 99%
“…It reaches the plasma membrane in a monomeric form. Its luminal release into the urine and subsequent polymerization is dependent on its cleavage mediated by the serine protease hepsin (107). Additionally, small amounts of UMOD are also released basolaterally into the interstitium and blood and show a positive association with kidney function (108).…”
Section: Uromodulinmentioning
confidence: 99%